IMPLEMENTASI LET’S DO IT WORLD DALAM MELAKSANAKAN WORLD CLEANUP DAY DI INDONESIA - Putriyolla, Teysya; Iskandar, Irwan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Environmental cleanliness is an urgency for all countries, including Indonesia, because Indonesia is one of the second largest plastic waste contributor countries in the world after China. This study describes how the involvement of Non-Governmental Organizations (NGOs) in handling environmental hygiene in Indonesia is carried out by Let's Do It Indonesia. This study uses a qualitative method with the level of group analysis. The author uses the theory of Global Civil Society (GSC). To analyze this case, the authors collect data from books, journals, websites, interviews, annual reports on the activities of Let's Do It World and Let's Do It Indonesia and official documents from Let's Do It World and Let's Do It Indonesia regarding the implementation of Let's Do It World in Indonesia. celebrating World Cleaning Day in Indonesia. The findings of this study resulted in several things. First: Let's Do It World carries out the world's largest social movement with the World Cleanup Day campaign. Second: With the world's largest gotong royong movement held simultaneously throughout the world, Let's Do It embraces the government, society and community to be more concerned about environmental cleanliness in Indonesia. Third: Let's Do It implementation in implementing World Cleanup Day was carried out before WCD activities, WCD activities took place and after WCD activities, this activity became a synergy momentum in commemorating world cleaning day to realize a clean Indonesia. Fourth: World Cleanup Day as a Global Civil Society movement means that all who participate in WCD gotong royong activities are global civil society and World Cleanup Day as an effort to voice international values.  Keywords: Implementation Let’s Do It World, NGO, World Cleanup Day.